The Unitary Executive Theory: An Attack on the Independence of Certain Federal Agencies or the Proper Exercise of Presidential Authority? - Hunter, Richard J.; Shannon, John H. (Archives of Business Research, 2025)
The assertion by President Donald J. Trump of authority to remove certain subordinate executive officers “without cause” has sparked a constitutional debate that literally began in 1789 at the founding of the Republic and has carried on until the present. Proponents of the doctrine of a “unitary executive” claim that the Constitution created a system of separated powers in which the President possesses plenary removal power, affording the President with “exclusive and total control” over all subordinates in the executive branch. Opponents cite the necessity of truly “independent agencies” designed for societal protections whose members are above politics and who can only be removed “for cause.” This paper explicates these issues in light of several Supreme Court opinions and offers examples of the constitutional and practical dangers associated with unfettered executive authority, as well as providing arguments in support of the doctrine.